Minutes of telephone conversations of John Foster Dulles and of Christian Herter (1953-1961) - Dulles, John Foster, 1888-1959; Herter, Christian Archibald, 1895-1966 (Presidential documents series., 1953)
Typescript minutes of the telephone conversations of Eisenhower's Secretaries of State in their official capacities, in reverse chronological order.